2011
DOI: 10.1017/s000711451000560x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea catechins on the pro-inflammatory response after haemorrhage/resuscitation in rats

Abstract: Plant polyphenols, i.e. green tea extract (GTE), possess high antioxidative and anti-inflammatory capacity, thus being protective in various models of acute inflammation. However, their anti-inflammatory effect and a feasible mechanism in haemorrhage/resuscitation (H/R)-induced liver injury remain unknown. We investigated the effects of GTE and the role of NF-kB in the pathogenesis of liver injury induced by H/R, and their effects on intercellular adhesion molecule-1 (ICAM-1) expression and neutrophil infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…This emphasizes the need for new treatment strategies to reduce oxidative stress in patients, e.g., smokers that are reported to have strongly elevated oxidative stress levels. GTE and its major components, catechins, have been attributed anti-oxidative properties in the past [27]. This is supported by the report of Wu et al describing GTE's potential to improve bone mineral density in habitual tea drinkers [30].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This emphasizes the need for new treatment strategies to reduce oxidative stress in patients, e.g., smokers that are reported to have strongly elevated oxidative stress levels. GTE and its major components, catechins, have been attributed anti-oxidative properties in the past [27]. This is supported by the report of Wu et al describing GTE's potential to improve bone mineral density in habitual tea drinkers [30].…”
Section: Discussionmentioning
confidence: 68%
“…Besides their function to directly scavenge ROS like the superoxide anion, oxygen singlet, and lipidic peroxyradicals, they can stabilize free ROS by means of hydrogenation or formation of complexes with oxidating species [23][24][25]. Based on that, polyphenols have been shown to have numerous biochemical and physiological benefits, including antioxidant, anti-microbial, anti-inflammatory, and cytoprotective activities [23,[26][27][28]. Clinical observations suggest that consuming green tea increases bone density and therefore reduces the risk of osteoporotic fractures [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, reduced tissue infiltration by neutrophils was closely associated with decreased CD54 expression (47). Jonsson and Palmblad have demonstrated that increased CD54 expression in HUVECs after stimulation with LPS resulted in enhanced adhesion rates of neutrophils to endothelial monolayers (22).…”
Section: Discussionmentioning
confidence: 95%
“…Sections were counterstained with hematoxylin. Polymorphonuclear leukocytes were determined by counting the number of CAE positive cells in a total of 25 high power (400x) fields per lung section per pig in a blinded manner as described before [36]. Both lung lobes are included in the evaluation.…”
Section: Detection Of Polymorphonuclear Leukocytesmentioning
confidence: 99%